2019
DOI: 10.1177/1748006x19844785
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective optimization of reliability–redundancy allocation problems for serial parallel-series systems based on importance measure

Abstract: For complex equipment, designers are challenged to reduce the expense while satisfying high requirements of system reliability. This article focuses on the multiobjective reliability–redundancy allocation problem for serial parallel-series systems to balance the conflicts between system reliability and design cost. The multiobjective reliability–redundancy allocation problem model for serial parallel-series systems is established with constraints on system reliability and design cost. An importance measure–bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These multi-objective problems are regarded as non-deterministic polynomial-time (NP)-hard problems, which should be solved by some evolutionary algorithms. 27,28 For reconfigurable systems, electrical distribution network reconfiguration with constraints of the system reliability and the power loss was optimized by an enhanced GA. 3 A robust optimization algorithm based on hybridization of a shuffled frog leaping algorithm and particle swarm optimization was developed to obtain the optimal distribution feeder reconfiguration, which could satisfy both operation and security expectations. 29…”
Section: Introductionmentioning
confidence: 99%
“…These multi-objective problems are regarded as non-deterministic polynomial-time (NP)-hard problems, which should be solved by some evolutionary algorithms. 27,28 For reconfigurable systems, electrical distribution network reconfiguration with constraints of the system reliability and the power loss was optimized by an enhanced GA. 3 A robust optimization algorithm based on hybridization of a shuffled frog leaping algorithm and particle swarm optimization was developed to obtain the optimal distribution feeder reconfiguration, which could satisfy both operation and security expectations. 29…”
Section: Introductionmentioning
confidence: 99%
“…In the recent literature, numerous importance measures have been introduced for binary systems, and they are applicable in several phases of different systems design such as telecommunication, transportation, energy (including petroleum and nuclear), health, risk analysis, etc. An extensive review of importance measures can be found in Borgonovo, Kuo and Zhu, Amrutkar and Kamalja, and Zhao et al [1][2][3][4][5] In probabilistic safety assessment, Borgonovo 1 and Vaurio 6 considered the roles of several importance measures. While previous research has mainly concentrated on component importance measures, [7][8][9][10][11][12][13] the importance measure of minimal path sets, 14 as required in the context of complex systems, has received very little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Natvig [23] raised the dynamic and stationary importance measures in repairable and nonreparable multistate coherent systems. Zhao et al [45] introduced the redundancy importance measure into the multi-objective optimization of reliability-redundancy allocation problems for serial parallel-series systems. Si et al [29] proposed the concept of integrated importance measure, which concerned the probability distributions and transition intensities of the component states simultaneously.…”
Section: Introductionmentioning
confidence: 99%